Fuzzy Inference System Menggunakan Metode Tsukamoto Untuk Menentukan Tingkat Kompetensi Pedagogik Guru - Anton Suroto; Hindayati Mustafidah (Sainteks, 2016)
As an educator, teacher must have pedagogic competence, personality competence, social competence, and professional competence to do the task. To know how important pedagogic competence point of teacher it’s needed difficulties accounting, so it has been made online application by using Fuzzy Inference System(FIS) use Tsukamoto Method which be able to access by whoever and whereever. Point of pedagogic competence can be gotten from input of scores in each aspect of pedagogic competence, then output of result is a point which indicate pedagogic competence level of teacher. Key words: Fuzzy Inference System, Tsukamoto Method, Pedagogic Competence, online.